2013
DOI: 10.1371/journal.pone.0061494
|View full text |Cite|
|
Sign up to set email alerts
|

Modulatory Effects of the Piccolo Genotype on Emotional Memory in Health and Depression

Abstract: Major depressive disorder (MDD) has been associated with biased memory formation for mood-congruent information, which may be related to altered monoamine levels. The piccolo (PCLO) gene, involved in monoaminergic neurotransmission, has previously been linked to depression in a genome-wide association study. Here, we investigated the role of the PCLO risk allele on functional magnetic resonance imaging (MRI) correlates of emotional memory in a sample of 89 MDD patients (64 PCLO risk allele carriers) and 29 hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 60 publications
(63 reference statements)
3
32
1
Order By: Relevance
“…Additional studies utilizing the candidate gene approach suggest a role for COMT (encoding catechol-O-methyltransferase), PRKCA (encoding protein kinase C, alpha), PCLO (encoding piccolo, which is involved in monoaminergic neurotransmission), and NR3C1 (encoding nuclear receptor subfamily 3, group C, member 1, i.e., the glucocorticoid receptor) in differential aversive memory capacity in healthy individuals [58,59 , [60][61][62].…”
Section: Candidate Genesmentioning
confidence: 99%
“…Additional studies utilizing the candidate gene approach suggest a role for COMT (encoding catechol-O-methyltransferase), PRKCA (encoding protein kinase C, alpha), PCLO (encoding piccolo, which is involved in monoaminergic neurotransmission), and NR3C1 (encoding nuclear receptor subfamily 3, group C, member 1, i.e., the glucocorticoid receptor) in differential aversive memory capacity in healthy individuals [58,59 , [60][61][62].…”
Section: Candidate Genesmentioning
confidence: 99%
“…The third most significant single nucleotide polymorphism (SNP, rs2522833) coded for a non-synonymous amino acid change (p.Ser4814Ala) in the C2A domain of Piccolo. The association with MDD was independently reproduced by others (Hek et al, 2010;Aragam et al, 2011;Woudstra et al, 2012Woudstra et al, , 2013Verbeek et al, 2013), although it was not replicated in the more recent and largest GWAS to date (Ripke et al, 2013). A recent replicate case-control study (Minelli et al, 2012) investigated depression-related personality traits in healthy subjects as a function of the PCLO rs2522833 genotype.…”
Section: Introductionmentioning
confidence: 95%
“…This study showed that rs2522833 homozygotes were more frequent among MDD patients than in controls (p < 0.01). Minor allele carriers appeared to have increased vulnerability to depression, including higher harm avoidance and lower novelty seeking (more fearful and fatigable), altered emotional memory (Woudstra et al, 2013) and altered amygdala function during fearful facial processing (Woudstra et al, 2012). These findings provided further support for the involvement of the PCLO C2A domain in MDD pathogenesis, although the association was not always replicated in subsequent GWAS (Lewis et al, 2010;Muglia et al, 2010;Rietschel et al, 2010;Kohli et al, 2011;Shi et al, 2011;Shyn et al, 2011;Wray et al, 2012), and suggest that it may act by influencing personality traits that increase the risk of developing MDD.…”
Section: Introductionmentioning
confidence: 96%
“…In line with the Woudstra and colleagues [39] study, we also examined the two samples together. Because of their known effect on cognitive functioning and emotional processing, age and sex were included as covariates in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Testing for Hardy–Weinberg equilibrium did not show deviation from the expected distribution of genotypes in healthy individuals, N = 351, χ 2  = .10, df = 1, p  = .75, nor in remitted patients, N = 320, χ 2  = .03, df = 1, p  = .85. Genotype groups were created in line with Woudstra and colleagues [39] and the association with depression: ‘C’ risk allele carriers (homozygous and heterozygous for C allele) versus ‘A’ non-risk allele carriers (homozygous for A allele).…”
Section: Methodsmentioning
confidence: 99%